Agricultural Research Expenditures in the United States: A Public Goods Perspective - Khanna, Jyoti; Huffman, Wallace E.; Sandler, Todd (The Review of Economics and Statistics, 1994)
Jyoti Khanna, Wallace E. Huffman, Todd Sandler, Agricultural Research Expenditures in the United States: A Public Goods Perspective, The Review of Economics and Statistics, Vol. 76, No. 2 (May, 1994), pp. 267-277